The Effect of Socio-Scientific Issue-Based Learning on Students’ Argumentation Skills in Science Education: A Meta-Analysis - Luh Putu Sathya Dewi; I Wayan Redhana; I Nyoman Tika (Postgraduate, University of Mataram, 2025)
Scientific argumentation is a crucial 21st-century skill in science education, yet many Indonesian students still struggle to construct evidence-based arguments. This study conducted a meta-analysis to evaluate the effect of Socio-Scientific Issue (SSI)-based learning on students’ argumentation skills. Twelve primary studies that met the inclusion criteria were analyzed using Comprehensive Meta-Analysis (CMA) software, with effect sizes calculated using Hedges’s g. The analysis revealed very high heterogeneity among the studies (I² = 96.56%), indicating substantial variation in results. Under the random-effects model, which is more appropriate in this condition, the pooled effect size was negative and not statistically significant (ES = -0.588, p = 0.16). Although the fixed-effect model produced a significant positive effect (ES = 0.329, p = 0.000), this result is less reliable because it does not account for the high variability across studies. Publication bias tests suggested potential bias but did not alter the overall interpretation. These findings indicate that the effectiveness of SSI-based learning on argumentation skills is inconsistent across contexts. Therefore, while SSI-based learning shows potential in specific settings, its overall impact remains uncertain and requires cautious interpretation.